1984
DOI: 10.1111/j.1440-1819.1984.tb00353.x
|View full text |Cite
|
Sign up to set email alerts
|

An Investigation on Sleep Disturbance of Autistic Children

Abstract: For the purpose of clarifying the pathophysiological meaning of sleep disturbance in autistic children, the sleep pattern of 75 such children was examined by a questionnaire method. Forty‐nine of them showed sleep disturbance in their early life with an incidence of 65%. The poorly‐developed group showed a high rate of sleep disturbance as compared with the relatively well‐developed group. There was a negative correlation between the developmental level and duration period of sleep disturbance. The investigati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
54
3

Year Published

2006
2006
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(60 citation statements)
references
References 8 publications
3
54
3
Order By: Relevance
“…Occurrence of sleep disorders has been considered to be relatively specific to children with autism compared to both typically developing children and children with intellectual disabilities without autism (Richdale and Prior 1995). The main manifestations are irregularity in sleep/wake pattern, sleep onset problems, frequent and prolonged night-time awakenings or early morning awakenings, period of drastically reduced sleep and poor sleep routines (Hoshino et al 1984;Wiggs and Stores 2004;Williams et al 2004). Even though some sleep disorders might be behavioural in origin (as in the typically developing children with poor sleep hygiene), circadian rhythm disturbances have frequently been reported in children with autism (Patzold et al 1998;Wiggs and Stores 2004).…”
mentioning
confidence: 98%
“…Occurrence of sleep disorders has been considered to be relatively specific to children with autism compared to both typically developing children and children with intellectual disabilities without autism (Richdale and Prior 1995). The main manifestations are irregularity in sleep/wake pattern, sleep onset problems, frequent and prolonged night-time awakenings or early morning awakenings, period of drastically reduced sleep and poor sleep routines (Hoshino et al 1984;Wiggs and Stores 2004;Williams et al 2004). Even though some sleep disorders might be behavioural in origin (as in the typically developing children with poor sleep hygiene), circadian rhythm disturbances have frequently been reported in children with autism (Patzold et al 1998;Wiggs and Stores 2004).…”
mentioning
confidence: 98%
“…Relationships have been found between sleep problems in children with ASD and increased rates of overactivity (Hoshino, Watanabe, Yashima, Kaneko & Kumashiro, 1984), disruptive behavior (Patzold, Richdale & Tonge, 1998), communication difficulties (Segawa, Katoh, Katoh & Nomura, 1992), social difficulties (Segawa et al, 1992) and difficulties with breaking routines (Segawa et al, 1992) (as cited in Schreck, Mulick & Smith, 2004). Schreck et al (2004) found that fewer hours of sleep per night predicted overall autism severity scores and social skills deficits.…”
mentioning
confidence: 99%
“…[2][3][4] Sleep-onset and maintenance insomnia are the primary sleep problems reported by parents of children with ASDs. [4][5][6] Additionally, children with ASDs experience irregular sleep-wake patterns, early morning awakenings, and poor sleep routines.…”
mentioning
confidence: 99%